2011
DOI: 10.1002/chem.201101114
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic SnX‐Complex‐Induced 1D, 2D, and 3D Copper Sulfide Superstructures from Anisotropic Hexagonal Nanoplate Building Blocks

Abstract: A facile route was demonstrated for inorganic Sn-X-complex-induced syntheses of self-assembled 1D columnar, 2D raftlike, and 3D stratiform anisotropic Cu(2)S hexagonal nanoplates. The factors (reaction time, temperature, the concentration of Sn-X complex, and so on) that influence the size, phase, monodispersity, and self-assembly ability of the Cu(2)S hexagonal nanoplates were studied in detail. It was found that the Sn-X complex could inhibit the growth of the <001> direction of monoclinic Cu(2)S nanocrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…To realize these applications, the size, shape, and polydispersity of the NC ensemble must be strictly controlled, as these characteristics are crucially important not only for the optoelectronic properties of the NCs themselves but also for the quality of the NC thin films obtained by solution‐based deposition techniques . This has motivated an extensive worldwide research effort into colloidal synthesis methods for Cu 2− x A NCs, which has resulted in a remarkable degree of control over the size and shape of colloidal Cu 2− x A NCs …”
Section: Binary Copper Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize these applications, the size, shape, and polydispersity of the NC ensemble must be strictly controlled, as these characteristics are crucially important not only for the optoelectronic properties of the NCs themselves but also for the quality of the NC thin films obtained by solution‐based deposition techniques . This has motivated an extensive worldwide research effort into colloidal synthesis methods for Cu 2− x A NCs, which has resulted in a remarkable degree of control over the size and shape of colloidal Cu 2− x A NCs …”
Section: Binary Copper Chalcogenidesmentioning
confidence: 99%
“…The compositional and structural diversity of binary copper chalcogenides creates a very rich parameter space that can be exploited to tailor the size and shape of colloidal Cu 2− x A NCs over a very wide range, opening up routes towards a plethora of morphologies not attainable for other binary semiconductor NCs. For example, nanodisks, nanoplatelets, (ultrathin) nanosheets, and other polyhedral shapes have been successfully synthesized with astonishingly narrow size and shape distributions (Figure ) . As will be discussed below, by strictly controlling the reaction conditions (e.g.…”
Section: Binary Copper Chalcogenidesmentioning
confidence: 99%
“…The ligand shell plays an important role in this self-assembly process. Li et al [41,60] demonstrated that a ligand shell composed of a Sn-complex can induce two-dimensional growth of copper sulphide particles and facilitate their selfassembly into one-, two-and three-dimensional nanostructures. Huang et al [62] showed that the ligand-induced self-assembly process can be reversible; they synthesized particles covered by dodecanthiol, which lay flat on the substrate, without any tendency to columnar self-assembly.…”
Section: Examples Of Self-organized Copper Sulphide Nanostructuresmentioning
confidence: 98%
“…In contrast to organic ligands, the inorganic ones can be considered as an electronically transparent "glue" rather than form an insulating layer around the nanocrystals. Li et al [41] conducted a systematic study, showing the influence of the Sn-thiolate complex on the size and the shape of copper sulphide nanocrystals. They could show that a higher concentration of the Sn complex resulted in the formation of larger and thinner nanoplates, which suggests that the Sn complex can inhibit the growth of the particles along the <001> direction, while it promotes the growth along the <100> and <010> directions.…”
Section: Colloidal Synthesis Of Copper Sulphide Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation